EFFECT OF FREEBOARD HIGH ON WAVE REFLECTION ON ZIGZAG MODEL WCSP-DS BUILDING - Prihatini, Wa Ode Zulia; Thaha, M A; Hatta, M P; Paotonan, Chairul (ASTONJADRO, 2022)
The Wave Catcher Shore Protection Dual-Slope (WCSP-DS) model in this study is a model of a dual function beach building as a beach protector and a catcher of wave energy, which has two walls, namely upright and inclined walls with an angle of 45°. The WCSP-DS building also has a reservoir at its top to accommodate wave runoff (overtopping). This study aims to determine the reflection in front of the model with variations in the freeboard height of the Wave Catcher Shore Protection Dual-Slope (WCPS-DS) building in a zigzag position. The test was carried out using a 1:20 scale 3D physical model at the Coastal and Environmental Engineering Laboratory, Faculty of Engineering, Hasanuddin University, Makassar. Simulation and data acquisition were carried out in a wave basin measuring 15 meters long, 10 meters wide using a regular wave generation system and the wave height data on the wave probe was recorded automatically. The simulation was carried out with 5 variations of freeboard height on 3 variations of waves, namely wave height and period and 3 variations of water depth. The results showed that there was a significant effect of freeboard height, wave steepness and water level position on WCSP-DS vertical wall height or water depth relative to the wave reflection coefficient in front of the model. The value of the reflection coefficient (Kr) in the relationship between freeboard height and water depth (Fb/d) at a depth of 0.4 meters (d/z = 1.143) ranges from 0.42 – 0.74, at a depth of 0.35 meters (d /z = 1) ranged from 0.44 – 0.74 and at a depth of 0.3 meters (d/z = 0.857) ranged from 0.35 – 0.71.